Identification of wheat genes induced by Puccinia triticina - Neugebauer, Kerri Allison (Kansas State University, 2016)
Bread wheat (Triticum aestivum L.) is an important staple crop for 35% of the world’s population. One economically important pathogen of wheat is Puccinia triticina, the causal agent of leaf rust, can cause up to 50% yield loss during epidemics. Despite the lack of an alternate host to complete the sexual stages, P. triticina still has variation within the population, which can make achieving durable resistance difficult. This study aims to gain a better understanding of the P. triticina-wheat interaction by identifying wheat genes that are induced by individual and multiple races. Six P. triticina races were evaluated on a susceptible variety of wheat at six days post inoculation. RNA was sequenced and 63 wheat genes were identified that showed varying expression in response to the six P. triticina races. Fifty-four wheat genes were characterized during the first seven days of infection using real-time PCR. Race specific gene expression was found in three wheat genes with race differences on Lr2A, Lr2C, and Lr17A. Wheat genes that had similar expression in response to all six races were also identified. Seven of the characterized genes were then silenced using RNAi hairpin constructs. The transgenic plants were molecularly characterized and inoculated with a virulent P. triticina race in the T₂ generation. However, the endogenous genes were not silenced and the transgenic plants maintained susceptibility. A mutation approach was also used to identify wheat genes involved in infection. A mutant population of 3780 wheat plants was created using EMS. Fifteen hundred mutants from the M1 population were screened for plants with a different infection phenotype compared to the non-mutated control and 570 were selected. After two additional generations of selection, eight resistant mutants were obtained. The gene expression of the seven previously identified genes were evaluated and one mutant showed reduced expression of an ER molecular chaperone gene. This research uses a forward and reverse genetics approach to identify and evaluate the function of wheat genes in the wheat-P. triticina interaction. Although RNAi could not determine the gene function, the knockout mutant shows that the identified genes may have a crucial role in infection.
Keywords: Wheat; Leaf rust; Resistance